2015
DOI: 10.1038/ajg.2014.245
|View full text |Cite
|
Sign up to set email alerts
|

Medical Marijuana for Digestive Disorders: High Time to Prescribe?

Abstract: The use of recreational and medical marijuana is increasingly accepted by the general public in the United States. Along with growing interest in marijuana use has come an understanding of marijuana's effects on normal physiology and disease, primarily through elucidation of the human endocannabinoid system. Scientific inquiry into this system has indicated potential roles for marijuana in the modulation of gastrointestinal symptoms and disease. Some patients with gastrointestinal disorders already turn to mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 73 publications
0
34
0
1
Order By: Relevance
“…53 Two recently published review articles on medical marijuana for digestive disorders and select neurologic disorders generally noted small numbers of studies and mixed results. 54,55 There are no published studies on the use of cannabinoids or marijuana to treat health conditions in children or adolescents.…”
Section: Research Findings On Pharmaceutical Cannabinoids and Medicalmentioning
confidence: 99%
“…53 Two recently published review articles on medical marijuana for digestive disorders and select neurologic disorders generally noted small numbers of studies and mixed results. 54,55 There are no published studies on the use of cannabinoids or marijuana to treat health conditions in children or adolescents.…”
Section: Research Findings On Pharmaceutical Cannabinoids and Medicalmentioning
confidence: 99%
“…Both CB1 and CB2 receptors are weakly expressed in the normal pancreas, but this expression increases in the setting of inflammation. CB1 receptor activation has shown to induce fibrosis while activation of CB2 receptor is linked with antifibrogenic effects in the pancreas (1,20). Matsuda et al (24) showed that down regulation of endocannabinoid system by AM251 (a CB1 receptor inhibitor) improved survival in rats with severe AP.…”
Section: Discussionmentioning
confidence: 99%
“…Most data of the effect of cannabis on AP comes from mice experimental models but the evidence of this data is conflicting (20). There are two G proteincoupled cannabinoid receptors in the human body, CB1 and CB2 receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] However, long-term administration of cannabinoids for either medical or recreational purposes induces rapid development of tolerance (a demonstration of physical dependence), which is a limitation and concern of its medical use and may lead to addiction and withdrawal symptoms. 5,6 Clinical data showed that 9% of adult cannabis users, and 17% of adolescent users, develop dependence and addiction after repeated dosage, 6 which is not trivial given the widespread usage of illicit cannabinoids in many countries.…”
Section: Introductionmentioning
confidence: 99%